Preparation and Quality Evalution of Amala (Phyllanthus emblica L.) Fruit Leather - Guragain, Nabin; KC, Yadav (NUTA Journal, 2020)
Preparation and quality evaluation of amala (Phyllanthus emblica L.) fruit leather from chakaiya variety was done. The amala pulp and sugar were mixed separately at the proportion of 50:50, 65:35, 57.5:42.5, 80:20, and 72.5:27.5 to prepare leather and labeled as samples A, B, C, D and E respectively. Total soluble solids, acidity, pH, total ash, crude protein, crude fat, crude fiber, total sugar and vitamin C content of each product samples prepared were determined. For sensory analysis, 9-point hedonic rating test was carried out. Sensory evaluation showed that all the sensory attribute scores were significantly higher (P<0.05) in leather prepared by using 65 parts and 57.5 parts amala pulp. The chemical analysis of leather samples showed that crude fat (0.26±0.02%), crude protein (1.60±0.06%), crude fiber (4.78±0.06 %), total ash (2.29±0.04%), acidity (2.60±0.01%) and vitamin C (394.37±0.6 mg/100 g) were significantly higher (P<0.05) in leather prepared by using amala pulp: sugar ratio of 80:20. But, total soluble solids (67±0.5 °Bx), energy value (382.60±0.95 Kcal/100 g) and total sugar (88.82±1.12%) were significantly higher in leather prepared by using 50 parts amala pulp. However, nutritional characteristics in sample B (65 parts pulp) were significantly higher than that of sample C (57.5 part pulp) so that sample B was selected as the best of all the samples.